DEMOGRAPHIC AND PROFESSIONAL FACTORS AS PREDICTORS OF COMMUNICATION SATISFACTION AMONG NIGERIA NATIONAL PARKS’ EMPLOYEES - Ogunjinmi, Adekunle Anthony; Ladebo, Olugbenga Jelili; Onadeko, Samuel Akinyele; Ogunjinmi, Oluwaseye Kehinde (European Scientific Journal, ESJ, 2013)
The study was on demographic and professional factors as predictors of communication satisfaction of Nigeria National Parks’ employees. It was conducted in the seven national parks in Nigeria. Data collection was through questionnaire administration. The questionnaire consisted of demographic factors of gender, age, and educational qualification; professional information such as work location, department, and work experience; and communication satisfaction items. Data was collected from 231 employees randomly selected from the estimated total number of employees (2000) in all the parks representing 11.6% of the total population. Data were presented descriptively and analysed with Pearson’s correlation and multiple linear regression. Results indicated that the employees were satisfied with 4 items of communication satisfaction questionnaire (CSQ). There was significant relationship between education, department and work experience of the employees with communication satisfaction. Furthermore, education and department had the most significant relationships with communication satisfaction facets. Gender and education were the predictors of communication satisfaction with education being the strongest predictor. Efforts are required in improving communication satisfaction of the employees for enhancing operational and management efficiency of the organization since every individual within the organization is important to the fulfillment of organizational goals and objectives.